An experimental investigation on drilling of aluminum alloy (Al 7075) using high speed steel cutting tools - Abd Halim, Nor Farah Huda; Dahnel, Aishah Najiah; Ismail, Azwa Azmariza; Zainudin, Nur Amanina (The Mattingley Publishing Co., Inc., 2020)
Aluminum alloys 7075 have been increasingly chosen as a main part in aerospace industry due to its property which is low in weight but having high strength. This paper focuses on the effect of cutting parameters and cutting condition when drilling Aluminum alloy 7075 in terms of tool wear, surface roughness and hole circularity. The drilling was conducted using high speed steel (HSS) having point angle of 118 ° and 6 mm tool diameter. The drilling test was conducted with a constant feed rate of 0.15 mm/min, cutting speeds of 22,44 and 66 m/min, and different cutting conditions (dry and cutting fluid). Drilling Aluminum Alloy 7075 with presence of cutting fluid and low cutting speed (22 m/min) resulted in reduced tool wear by 20 to 30 % and improved surface roughness by 30 % as compared to drilling in dry condition with same cutting parameter..